Modifikasi dan Karakterisasi Kitosan dari Limbah Cangkang Kepiting Bakau Asal Kabupaten Maluku Tenggara sebagai Adsorben Logam Pb dan Cd - RACHMIN MUNADI; YUSAFIR HALA; FANDI JAKA BIMANTARA (UIN Sunan Gunung Djati Bandung, 2022)
Mangrove crab is one of the marine animals that is quite economically valuable that lives in a mangrove environment (mangrove forest). Mangrove crabs are also consumed by the community, especially people in coastal areas. Crab shells containing the chemical compounds chitin and chitosan are waste that is easily available and available in large quantities, which so far has not been optimally utilized. Chitosan isolated from crab shells can be used as heavy metal adsorbents. The aim of this research was to determine the modification and characterization of chitosan from mangrove crab shell waste as Pb and Cd metal adsorbents. The research methods included of deproteination with 1 M NaOH, deminnarization with 1 N HCl, decolorization with NaOCl. Modification of chitosan in the deacetylation process using NaOH 60% was varied. The characterization of chitosan were moisture, solubility, ninhydrin test, and deacetylation degree using FTIR. Determination of the adsorption capacity of crystalline to metall using atomic absorption spectrophotometry (AAS). Samples were obtained from Evu Village, Southeast of Maluku. Based on data analysis and discussion, it can be seen that the appropriate water content at 3x 1 hours is 7,63%, completely dissolves in 2% acetic acid, positive purple ninhydrin test , and a good degree of deacetylation at 3x 1 hour modification.